Barrier Lyapunov functions-based command filtered output feedback control for full-state constrained nonlinear systems. (July 2019) - Yu, Jinpeng; Zhao, Lin; Yu, Haisheng; Lin, Chong
Abstract: In this paper, an adaptive output feedback control via command filtered backstepping is proposed for a class of uncertain nonlinear systems with full-state constraints. Firstly, the "explosion of complexity" problem inherent in all the existing results of backstepping-based full-state constraints area is solved by the proposed control. Secondly, a state observer is designed to estimate the immeasurable states and the command filtered technology is utilized to cope with the problem in the present backstepping-based results of constrained nonlinear systems. Thirdly, the barrier Lyapunov functions are constructed to ensure the constraints are not transgressed. Then, an error compensating mechanism is developed to cope with filtering errors and only one adaptive law is needed for the full-state constrained nonlinear systems. An example is given to illustrate the validity and potential of the new design scheme.